The Impact of Mobile Banking Services on Customer Loyalty at PT. Bank Syariah(Study of PT. Bank NTB Syariah KCP Lopok) - Dwi Maulini, Yuni; Selva, Selva; Hidayati Indra Ningsih, Nurul; Reinalda Tri Yunarni, Baiq (ICON Publisher, 2025)
Islamic banks in Indonesia have become an alternative for customers, both Muslim and non-Muslim. Islamic banking is regulated by Law No. 21 of 2008 concerning Islamic Banking. This study aims to analyze the influence of mobile banking services on customer loyalty at PT. Bank Syariah (a study of PT. Bank NTB Syariah KCP Lopok). This study uses a quantitative approach with data processing using SPSS. The results of this study indicate that customer loyalty to mobile banking services is influenced by several factors, both statistically significant and insignificant. System security shows a positive influence, although not significant, but remains crucial as a basis for long-term trust. Ease of use is proven to have a significant influence, because intuitive and user-friendly service design encourages comfort and customer engagement. Company credibility also has a positive influence, although not significant, but remains important in building a professional image and indirectly encouraging loyalty. Service speed is a significant factor that strengthens loyalty, because efficiency and responsiveness create a satisfying user experience. Overall, although mobile banking contributes to loyalty, its influence is still limited. Many aspects of loyalty are influenced by other factors such as face-to-face service, emotional connection, and product quality. Therefore, strategies to strengthen customer loyalty need to be implemented holistically, not only through optimizing digital services but also by considering the relationship elements and the overall customer experience. A combination of technological and humanistic approaches is key to building sustainable loyalty in the digital era.